Dynamics of Village Community Political Participation in the Digital Era: Problems and Solutions - Yumiriyah Abdullah (Ampera: A Research Journal on Politics and Islamic Civilization, 2024)
This research explores the dynamics of village community political participation in the digital era with a focus on the context of problems and solutions which are the subject of analytical study, then this research uses a qualitative descriptive-analytical method with a desk study approach. The findings indicate that village community participation in the digital era has two problems, namely lack of access to technology which has implications for a lack of understanding of the information obtained, where this connection is found through the village digital literacy index. The second is the low level of trust that exists, where village communities tend to be indoctrinated with unethical political behavior so that the tendency towards political promises that are initiated is not felt by village communities which ultimately gives rise to community distrust of certain political actors or figures. In the end, the solution designed requires efforts from the government to provide information-supporting infrastructure, digital literacy education, community involvement in the digital political process, and protection of community data in accessing information through the media.